Biomechanical analysis of crossed pinning construct in supracondylar fracture of humerus: does the point of crossing matter? - Abdul Razak, Ardilla Hanim; Ahmad, Muhammad Wafiuddin; Soldin, Mohd Aizat Azfar; Awang, Mohd Shukrimi; Nik Abdul Adel, Nik Alyani (Cureus Inc, 2021)
Abstract Introduction This appears to be the first biomechanical study that compares the stability of various locations of the crossing points in crossed pinning Kirschner wiring (K-wire) construct in treating pediatric supracondylar humerus fracture (SCHF). Additionally, this study compared the biomechanical stability between crossed pinning K-wire construct and the three-lateral divergent K-wire construct.